STRESS FIELDS AND GEOLOGICAL STRUCTURE OF WESTERN CLOSURE OF HORLIVKA ANTICLINE OF DONBAS PART 2. STRESS AND STRAIN FIELDS - NIKITENKO, Oleksandr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. In tectonophysical studies, particular importance is placed on the mechanism of formation of large complex deformation structural elements, and the Horlivka anticline of the Donets Basin serves as such an example. Its importance lies not only in its complex structural composition and development mechanism but also in its potential impact on safe and efficient coal mining. This study aims to analyse the geological structure, stress and strain fields of the western closure of the Horlivka anticline that could be useful in forecasting geological factors for coal mining operations.Methods. The paleostress analysis was performed on the collected fault orientation and kinematic data using Gushchenko's kinematic method based on the analysis of tectonic displacement vectors along slickensides. Mesoregional stress field characteristics were reconstructed by statistical processing of local stereographic solutions. The relative age chronology and staging of tectonic stresses were studied using the stress monitoring method. The characteristics of the principal axes of the total strain field were processed using the GEOS software. Results. Mesoregional stress field is characterised by a subhorizontal NW–SE-oriented maximum principal stress axis and a subhorizontal NE–SW-oriented minimum principal stress axis. This stress regime is classified as a strike-slip regime and is the youngest one (Alpine orogeny) for the Donets Basin. The evolution of tectonic loading conditions of the studied structure is characterised by a deformation series of six stress regimes from the oldest (normal) to the youngest (strike-slip). Stretching axis of the strain ellipsoid is oriented NW and N–S, and shortening axis is oriented NE, nearly orthogonal to the anticline axis. Strike- and oblique-slip faulting regimes of the total strain field were determined for most of the study area, and the deformation has occurred under shear conditions, as indicated by the Lode–Nadai coefficient. Conclusions. A structural pattern of deformation elements, including a conjugate strike-slip fault system of the shear zone, a dome-shaped fold, and longitudinal thrusts in its limbs, may be interpreted as a single pattern of structural paragenesis developed by right-lateral displacements along the longitudinal strike-slip fault system within the Horlivka anticline paraxial part. Fragments of mutual symmetry between the stress and strain fields can be taken as evidence of their genetic relationship.
Keywords: geological structure; shear deformation; kinematic indicator; stress field; brittle deformation field; kinematic method; Lode–Nadai